The Future of Coral Reefs Research Submitted to ICRS 2020, Bremen, Germany - Ormond, Rupert; Schupp, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This volume contains a series of papers prepared for presentation at the 14th International Coral Reef Symposium, originally planned for July 2020 in Bremen, Germany, but postponed until 2021 (online) and 2022 (in person) because of the COVID-19 pandemic. It contains a series of papers illustrating the breadth of modern studies on coral reefs and the response of the reef science community to the threats that coral reefs now face, above all from climate change. The first group of papers focus on the biology of a selection of reef organisms, ranging from sea fans to coral dwelling crabs. The next group describe studies of coral communities and ecological interactions in regions as diverse as Florida, Kenya, Colombia, and Norway. Further papers describe investigations into the effects of global warming (in the Maldives and in Timor-Leste) and of other impacts (UV blockers, ocean acidification). The final two papers describe the latest applications of satellite and camera technology to the challenge of mapping and monitoring reefs.